The effect of wind on historical timber towers analyzed by plastic limit analysis in the focus of a collapse. (April 2022) - Hegyi, Dezso; Armuth, Miklos; Halmos, Balazs; Marotzy, Katalin
Highlights: Historical timber roofs. Failure of timber roofs. Plastic limit analysis. Climate change. Change of meteorology loads. Abstract: Climate change severely impacts the architectural heritage. Old buildings may have survived many large storms and heavy snows in the past, but extremes have increased recently. Meanwhile, the condition of historical structures gradually degrades even if they have had regular maintenance. Church towers are strongly affected: they are subject to increased wind compared to the other parts of the building. They are in a high location and gain less attention because of their out-of-the-way position. On 17th September 2017, a massive storm in the Banat region, Romania, caused several church towers to collapse: the towers of Toager, Remetea Mare, Donceni and Ghilad fell down to pieces that day. The collapse of the tower of Dumbrava was one of the buildings involved, this study aims to clarify whether the poor condition of the building, or the flaw of the original design was the main reason for the failure in this village. The structural analysis of such historical timber structures can be problematic as the weak joints of the structure limit the load-bearing capacitance in an exceptionally low level if the traditional elastic analysis is used. The present paper points out that the plastic limit analysis can give a more realistic breaking load level for the high order statically indeterminate carpenter roofs.